A large proliferating trichilemmal cyst masquerading as squamous cell carcinoma - Kiran Alam; Kanupriya Gupta; Veena Maheshwari; Manoranjan Varshney; Anshu Jain; Arshad Hafeez Khan (Wolters Kluwer Medknow Publications, 2015)
Proliferating trichilemmal cyst (PTC), a rare benign tumor, is a fascinating follicular neoplasm. It occurs on head and neck region of elderly women and its histologic hallmark is trichilemmal keratinization. A 70-year-old female presented to skin outpatient department with complaints of a slowly growing mass on scalp for the past 2 years. On examination, the lesion was firm, mobile, painless, and measured 6 × 5 × 3 cm and was not fixed to the underlying bone. Laboratory investigations were unremarkable. Excisional biopsy was done. Histopathology revealed well-demarcated tumor with variably sized lobules of squamous epithelium undergoing an abrupt change into eosinophilic amorphous keratin without granular cell layer (trichilemmal keratinization). PTC should be differentiated from trichilemmal cyst as it has potential for malignant transformation. Thus, complete excision is recommended for all benign proliferating variants owing to their potential for locally aggressive behavior and malignant transformation.